1999
DOI: 10.1002/(sici)1097-4628(19990131)71:5<677::aid-app1>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Thin-film plasma-polymerized iso-t-pentinol and its postpolymerization properties

Abstract: Thin films of plasma polymer were prepared from unsaturated precursor with one triple bond, iso-t-pentinol. This precursor was injected either in a vapor state itself or using argon as a carrier gas, bubbled through a precursor. These polymers were prepared under different fixed conditions when only one parameter of plasma polymerization among all the others was changed in each measurement during the process of polymerization (i.e., power in a matched reactor, precursor partial pressure, total pressure in reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2001
2001

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Plasma polymers have been produced and analyzed from a wide variety of different monomers. In addition, workers have utilized different excitation regimes for their plasmas, and investigated the effect of deposition parameters upon the chemistry of the final product. It has been demonstrated that the chemistry of the final product can be significantly altered by controlling several deposition parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma polymers have been produced and analyzed from a wide variety of different monomers. In addition, workers have utilized different excitation regimes for their plasmas, and investigated the effect of deposition parameters upon the chemistry of the final product. It has been demonstrated that the chemistry of the final product can be significantly altered by controlling several deposition parameters.…”
Section: Introductionmentioning
confidence: 99%